Skill Heterogeneity and Aggregation Bias Over the Business Cycle - Prasad, Eswar (Washington, D.C. : International Monetary Fund, 1995)
This paper extends the equilibrium business cycle framework to incorporate ex ante skill heterogeneity among workers. Consistent with the empirical evidence, skilled and unskilled workers in the model face the same degree of cyclical variation in real wages although unskilled workers are subject to substantially higher procyclical variation in employment. Systematic cyclical changes in the average skill level of employed workers are shown to induce bias in aggregate measures of cyclical variation in the labor input, productivity, and the real wage. The introduction of skill heterogeneity improves the model's ability to match the empirical correlation between total hours and the real wage but the correlation between total hours and labor productivity remains higher than in the data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet